811 Dermal Fillers and Delayed Hypersensitivity Following Influenza Vaccine: A Case Report. (19th August 2022) - Magill, H; Ioannidi, L; Collier, J
Abstract: Background: Dermal fillers can be used to improve cosmetic appearance of facial soft tissue in patients with Human Immunodeficiency Virus (HIV) associated lipodystrophy. There are documented cases of delayed hypersensitivity reaction to dermal fillers following influenza-like illness, and similarly following coronavirus vaccination, however none following the influenza vaccine. Case: A 52-year-old female was treated with dermal filler injections to her zygomatic and buccal regions for lipoatrophy secondary to HIV treatment. Her HIV was well controlled with a low viral load. Six months following dermal filler treatment she presented with periorbital and zygomatic arch swellings one week after vaccination for influenza. The swelling was initially treated as periorbital cellulitis with antibiotics; however, it did not resolve. The swelling was in the same distribution as her filler and as it did not appear to be an infection but rather a delayed hypersensitivity reaction, it was treated with prednisolone for one week. There was further reduction in nodules following intralesional triamcinolone injections and following weaning of prednisolone there was no recurrence of swelling. Discussion: To our knowledge this is the first case of its type to be described; literature searching does not retrieve any reports to date of adverse events related to the influenza vaccine following the use of dermal fillers. This is an important consideration in terms of the risks posed by this treatment in immunocompromised patients, and detailed informed consent is an important component of treatment.